Mempertahankan Piil Pesenggiri Sebagai Identitas Budaya Suku Lampung - Fitra Endi Fernanda; Samsuri Samsuri (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
The Lampung tribe is a minority tribe established by Lampung Province. The Lampung Province became a destination for population migration, so Lampung was discussed by Javanese, Sundanese, Balinese and so on. As a minority tribe, the Lampung tribe needs to strengthen its cultural identity among the people so that the cultural values of the Lampung tribe are not lost. Piil Pesenggiri is a philosophy of life that has become the cultural identity of the Lampung tribe. The purpose of this study is to explain the principles of Piil Pesenggiri so that its values can be rebuilt. This article was written in the literature study method with a collection of various sources of books, journals and research on the Piil Pesenggiri. The results show four principles of Piil Pesenggiri that need to be revived, namely juluk adek, nemui nyimah, nemui nyapur and sakai sambyan. Cooperation between all parties, namely traditional leaders, community members, academics and the government, is needed to revive the principles of Piil Pesenggiri.